Challenges of religious integration among indigenous Muslim converts (Mualaf) in Sabah, Malaysia - Zaifuddin Md Rasip; Rahayu Handan; Mohd Zulfahmi Bin Mohamad; Amer Hudhaifah Hamzah (RSIS International, 2025)
The increasing number of Muslim reverts (Mualaf) in Sabah, particularly among indigenous communities, represents a distinctive trend within Malaysia’s religious demography. Unlike in Peninsular Malaysia, where conversions predominantly occur among non-indigenous populations, reversion to Islam in Sabah involves ethnic groups such as the Kadazan Dusun, Murut, Rungus, and Sungai. This unique pattern necessitates an in-depth exploration to understand the specific dynamics influencing these religious transitions. This qualitative study aims to investigate the factors contributing to the rising number of Mualaf among indigenous communities in Sabah, identify the principal challenges these converts face post-conversion, and critically evaluate the effectiveness of support mechanisms offered by religious institutions and non-governmental organizations (NGOs). Data were collected through semi-structured interviews with selected Mualaf from various indigenous backgrounds across Sabah, complemented by secondary sources such as governmental reports, academic publications, and NGO documents. The findings indicate that indigenous reverts encounter complex and multifaceted challenges, including bureaucratic hurdles during formal conversion procedures, psychological stress associated with identity realignment, rejection by family members and local communities, limited religious literacy, and inadequate access to structured Islamic educational resources, especially in remote rural areas. Moreover, the lack of culturally sensitive religious educators and persistent societal stigma exacerbate feelings of isolation, complicating their integration into the broader Muslim community. Consequently, this research underscores the urgent need for inclusive and contextually relevant da’wah strategies tailored to indigenous cultural contexts. Additionally, practical recommendations are proposed for policymakers, religious institutions, and civil society groups to improve existing support structures, foster religious resilience, and ensure sustainable spiritual growth and communal empowerment for indigenous Mualaf.